The Action of Bcl-2 Apoptotic Family Proteins and Caspases in Mediating Follicle Atresia in Adult Mouse - Liliana Petculescu-Ciochină (Scientific Papers Animal Science and Biotechnologies, 2011)
Among follicles present on the surface of the ovary only a small part reach ovulation, the majority entering atresia, which is an apoptotic process regulated hormonally in general. Apoptosis (from greek: apo = from, ptosis = falling) - is a normal physiological process, genetically programmed cell death, which carries energy consumption by activating a program of internal suicide. This occurs at each stage of follicular development and is accompanied by a significant reduction in the number of follicles present at birth. Development stage-dependent mechanisms coordinate the evolution of follicles, leading to ovulation of a very small number of them. At follicular level apoptosis involves many morphological and biochemical processes that are based on pro-and anti-apoptotic members of Bcl-2 family of proteins (located on mitochondrial outer membrane) and caspases. These changes aim internucleosomal DNA fragmentation, cell retraction followed by its wrinkling, cytoskeleton disruption, preservation of cytoplasmic organelles structure and function, loss of intercellular ties with the reduced expression of conexine 43 (key protein of communication junctions between granulose cells), progressive fragmentation of nucleus and cytoplasm, and finally the appearance of apoptotic bodies, and their inclusion by phagocytes, without the involvement of any inflammatory response.